Potential Utilization of Magnetic Generator Energy (EGM) as a Substitute for Alternative Energy Sources in the Steel Production Process of PT. XYZ - Indonesia - Moch Kuswanto; Abraham Benedict Cahyasusila; Rudy Agus Gemilang Gultom (Journal Research of Social Science, Economics, and Management, 2022)
The availability of raw material resources for the steel industry is one of Indonesia's supporting capacities to achieve steel industry independence. Indonesia has the largest iron ore processing company in Southeast Asia, namely PT. XYZ. Production activities of PT. XYZ includes the production of raw materials, the production and sale of semi-finished steel, and the production of steel such as steel billets, HRC and CRC, steel wire rods (WR), reinforcing steel, profile steel, and steel pipes according to the specifications required by consumers. The fulfillment of industrial production capacity cannot be separated from energy needs. Reducing costs in the energy sector without reducing production capacity is one solution in increasing production capacity. This research was conducted to determine the potential use of magnetic generators as a strategy to increase production efficiency of PT. XYZ by using the theory of cost effectiveness. This research was conducted through discussions with various related parties and stakeholders in order to determine the standard requirements for the type of energy supply for industry. Then, a literature study related to the supply of energy types was carried out in accordance with the limitations of the problem, namely the energy potential of a magnetic generator. Based on the results of the research and discussion that have been described, it can be concluded that the analysis of the break-even point of EGM and existing electrical energy shows that EGM with a capacity of 10 kW is able to achieve profits after a minimum steel production capacity of 2,055.94 tons and a return on investment in the third year which means more faster than the theoretical service time capability of 20 years. By considering the results of the break even point (BEP) and cost effectife analysis (CEA) analysis, it is concluded that from the economic aspect, EGM has the potential as an alternative to substitute new energy sources at PT. XYZ.